2019
DOI: 10.3390/su11174662
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction and Assessment of the Impacts of Soil Sealing on Agricultural Land in the North Nile Delta (Egypt) Using Satellite Data and GIS Modeling

Abstract: Soil sealing is currently one of the most critical barriers to sustainable development, particularly in developing countries such as Egypt. Agriculture is a major component of the Egyptian economy and the country’s main source of food security. Urbanization is devouring vast areas of agricultural land, and therefore, in the present study, urbanization was used to determine the degree of soil sealing in a region of Kafr El Sheikh Governorate, Egypt. In this work, remote sensing data were used to monitor changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 50 publications
(23 reference statements)
6
18
0
Order By: Relevance
“…4). These results correspond well to the findings of (Wahren et al 2009, Abu-Hashim 2011Elkhrachy 2015;Hendawy et al 2019) who reported that land use has a positive impact on soil infiltration. Moreover, the variation in infiltration capacity is largely related to land management and human activity as well as soil characteristics.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4). These results correspond well to the findings of (Wahren et al 2009, Abu-Hashim 2011Elkhrachy 2015;Hendawy et al 2019) who reported that land use has a positive impact on soil infiltration. Moreover, the variation in infiltration capacity is largely related to land management and human activity as well as soil characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…The results show that land use has significant impacts on infiltration rate and soils holding capacity as these results associated with human activities in two directions positive and negative impact. The positive impact was noted in the area demonstrated by good agricultual practice and management, meanwhile the negative impacts were noted in the area characterized by urban sprawl (Hendawy et al 2019;Abu-Hashim 2011). That the paved surfaces and rooftops did not allow water to penetrate in soil causing direct surface runoff, and these approaches showed with the illustrated results that the highest value of the direct surface runoff was distinguished around urban areas where it ranged between 40-50 and 50-58 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Soil function is generally threatened by increased food demands, human influence, and its activities (such as the continuous irrigation with low quality water), as well as land use and climate change [97,98]. This may lead to physical and chemical degradation processes and negatively affect soil sustainability [99,100]. Monitoring land use/land cover changes is fundamental for sustainable irrigation water management plans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, integrated GIS and geostatistical analyses can be useful for assessing the spatial variation of soil properties and predicting them in unsampled locations. For example, the use of variogram analyses can capture and accurately map the complex spatial relationships between soil data layers [21][22][23]. Kriging is one of the most commonly used interpolation methods [24], and it can suitably support precise farming based on the identification of homogeneous sub-sets of similar yield-limiting factors [25,26].…”
Section: Introductionmentioning
confidence: 99%